Investigating the effect of educational intervention on knowledge, attitude and practice (KAP) related to the educational curriculum of anesthesiology residents - Mafi, Amir Ali; Vosooghian, Maryam; Dahi, Mastaneh; Moshari, Mohammadreza (Researcher Bulletin of Medical Sciences, 2024)
Objective: Anesthesiology is a medical specialty that prepares medical doctors to diagnose, treat, and care for patients. It is essential for the educational content of anesthesiology residency programs to encompass assessment, preparation, counseling, and education. This study aimed to evaluate the impact of an educational intervention on the knowledge, attitude, and practice (KAP) of anesthesiology residents regarding their training program. Materials and Methods: Participants in this study were randomly assigned to one of two groups: an intervention group (N=22) receiving educational training and a control group (N=23) receiving no intervention. All participants completed a demographic questionnaire online, followed by an initial KAP assessment. The intervention group then participated in online training that covered the principles, rationale, therapeutic roles, responsibilities, and curriculum expectations of the anesthesiology program at Shahid Beheshti University of Medical Sciences. One month after the training, the KAP questionnaire was administered again to evaluate changes. Results: The study found that, at the conclusion of the intervention, the intervention group demonstrated significantly higher scores in knowledge (P=0.010), attitude, practice, and overall KAP (P < 0.001) compared to the control group. Intragroup analyses also revealed significant improvements in KAP for both groups throughout the study; however, the magnitude of these changes was markedly greater in the intervention group (P=0.01). Conclusion: The findings indicate that anesthesiology residents initially had low levels of knowledge and positive attitudes toward their curriculum, which improved significantly following the educational intervention. Ongoing training for graduates in this field is crucial to ensure effective implementation of the curriculum, ultimately leading to the development of qualified anesthesiology professionals in the country.